Analisis Analisis Tingkat Kenyamanan Rumah Sakit Di Kota Makassar (TIPE A DAN TIPE B) Dengan Konsep Pendekatan Arsitektur Bioklimatik - Ashari Abdullah; Rohana; Sumarni; Hamkah; Ruslan (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2023)
Makassar City has hospitals spread across several sub-districts, with categories of type A-E, but it is unknown whether the currently operating hospitals use the concept of a bioclimatic approach or only meet service standards from the aspect of medical needs. The aims of the study were: to determine the comfort level of the hospital (type A and type B), to formulate a hospital planning strategy with the concept of a bioclimatic approach to buildings through design recommendations. Case research methods (field studies and literature) and descriptive were used in the research. The results and discussion are: Several type A hospitals apply the bioclimatic concept based on an analysis of the level of comfort and service, for example the Wahidin Sudirohusodo hospital for the public, the Tabjuddin Chalid hospital for lepers and the Dadi hospital for mental disorders. Overall, each building has a different analysis and adjusts the comfort of space that is environmentally friendly, and has humanist characteristics towards outdoor space and the environment. Whereas type B hospitals, which apply bioclimatic concepts such as: Awal Bros Hospital, Labuang Baji Hospital, Anak Pertiwi Hospital, each of which has comfort from a unique spatial aspect, adjusts to the level of patient needs, creates good comfort and safety. For the planning strategy for the concept of Bioclimatic Architecture, it is desirable that the shape of the building must be sturdy, have many cavities, facades and the environment that affect the design of the building, the building is more environmentally friendly, comfortable and safe and more efficient in energy use.